John Locke - Mack, Eric, 1946- (Major conservative and libertarian thinkers ;, 2009)
John Locke (1632-1704), one of the great philosophers, is probably best known for his contributions to political thought. In this outstanding volume, Professor Eric Mack of Tulane University explains Locke's philosophical position, placing it in the tumultuous political and religious context of 17th century England. For Locke, entering into political society did not involve giving up one's natural rights, but rather transferring to governmental authority the job of protecting those rights. In this rigorous critical analysis, Mack argues that Locke provides an impressive - if not decisive - phi.